River lamprey present an unusual predation threat to Atlantic salmon smolts in Lough Neagh, Northern Ireland. Issue 4 (1st September 2020) - Kennedy, Richard J.; Campbell, Warren; Gallagher, Kevin; Evans, Derek
Abstract: A new monitoring programme on the Lough Neagh catchment has documented a high incidence of river lamprey, Lampetra fluviatilis L., predation on Atlantic salmon smolts, Salmo salar L. In total 470 smolts were examined during the 2020 emigration period with 168 fish (36%) exhibiting lamprey scars of which 57 were lightly scarred and 111 were classed as heavily scarred. Lamprey predation was not size selective on Lough Neagh S. salar smolts.